2019
DOI: 10.1029/2019jb018339
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Seismic Monitoring of a Shear Fault Within a Floating Ice Plate

Abstract: The deformation of a circular fault in a thin floating ice plate imposed by a slow rotational displacement is investigated. Temporal changes in shear strength, as a proxy for the resistance of the fault as a whole, are monitored by the torque required to impose a constant displacement rate. Micro-seismic monitoring is used to study the relationship between fault average resistance (torque) and micro-ruptures. The size distribution of ruptures follows a power-law scaling characterized by an unusually high expon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 107 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, it was confirmed that the MS parameters, such as amplitude, event number and frequency, which could reflect the quantity, size and direction of microcrack propagation, had a great relevance on damage degree of coal and rock [20][21][22][23]. The actual MS signals contain a great amount of noise whose interference often results in the difficulty of the signal processing.…”
Section: Introductionmentioning
confidence: 86%
“…In previous studies, it was confirmed that the MS parameters, such as amplitude, event number and frequency, which could reflect the quantity, size and direction of microcrack propagation, had a great relevance on damage degree of coal and rock [20][21][22][23]. The actual MS signals contain a great amount of noise whose interference often results in the difficulty of the signal processing.…”
Section: Introductionmentioning
confidence: 86%